A Systematic Literature Review of Creative Placemaking on Creative Approaches in Thematic and Contextual Settings - Rosetia, Amanda; Harun, Nor Zalina (Departement of Architecture, Universitas Islam Indonesia, 2026)
This study demonstrates that several key elements, including economic development, art and cultural engagement, participatory stakeholder involvement, and collaborative management, intersect with the concept of creative placemaking. This intersection suggests that, as the creative placemaking process impacts a wide array of interests, the reinforcement of creativity has, in some cases, diminished the recognition of its foundational contributions. The aim of this study is to explore how innovative placemaking can support regenerative strategy in development within a specific or thematic context, such as historical or protected sites. This research focuses on innovative placemaking strategies as essential components of notable socio-spatial concepts in specific geographies, including their unique natural features. To achieve this, a systematic literature review was conducted, examining creative placemaking research from around the world across all times. The review followed the PRISMA 2020 guidelines and utilized three major academic databases: Scopus, Web of Science (WOS), and Science Direct. Through the process, five key thematic areas of creative placemaking were identified: (1) Cultural well-being, (2) Income generation, (3) Sectoral inclusion, (4) Art and creative endeavours, and (5) Context-specific settings. The primary aim of this study is to address a gap in the literature on creative placemaking, particularly in specialized or themed contexts, contributing to a more profound understanding of its role on contributed dimension in regenerative strategy.